Examining Blockchain Platforms: Finding the Perfect Fit for Various Topics - Adil El Mane; Younes Chihab (International Journal of Advanced Science and Computer Applications, 2026)
This research compares some of the most well-liked Blockchain platforms. Depending on the orientation and the target domain, it greatly varies from one to the next. To offer readers a thorough grasp of the advantages and disadvantages of each platform, essential elements, including scalability, security, interoperability, and administration, are explored. The researchers who want to investigate the best user interface for developing and generating their Blockchain architecture quickly, analysing the nodes, saving transactions, and spreading data to all network members will benefit from comparisons between Blockchain platforms before and after. This paper will assist researchers in learning more about Blockchain platforms, their configuration/installation difficulty, and other details like the programming languages used in the structure, the description, and the outcome of a medium to expert IT researcher and the challenges that surpass him during the installation phase. Researchers will value this concept since it will save them money and time.